Dampak Pandemi COVID-19 Terhadap Loyalitas Pelanggan pada Beverage Shop di Onezo Indonesia - Stephanie Rosanto; Novy Ratna Sari (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The food and beverage (F&B) industry is one of the sectors affected by the COVID-19 pandemic. The prohibition of large-scale social interactions in the community, such as holding gatherings during the Large-Scale Social Restrictions (Pembatasan Sosial Berskala Besar / PSBB) period established by each region, has also contributed to the sharp decline in food and beverage sales. The total average result of the COVID-19 Pandemic Impact (X) variable questionnaire in OneZo Indonesia is 67% which is in the good category. Of all the statement indicators, it can be seen that the lowest indicator is